Application of equilibrium passive sampling to assess the influence of anthropogenic activities and bioturbation on the distribution of hydrophobic organic chemicals in North Sea sediment cores. (1st February 2023) - Kreutzer, Anne; Reininghaus, Mathias; Meyer, Julia; Kröncke, Ingrid; Seiler, Thomas-Benjamin; Hollert, Henner; Witt, Gesine
Abstract: The pollution state in the German Bight was investigated by determination of pollutant concentrations of sediment samples using equilibrium passive sampling. Polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAH) were determined in the pore water of North Sea sediment. The freely dissolved pore water concentration (Cfree ) was measured applying Solid Phase Microextraction (SPME) by using PDMS-coated glass fibers. The obtained results show that the North Sea contamination level with the investigated pollutants is relatively low. However, the stations close to the sediment-dumping site were higher contaminated. A macrofauna analysis showed that bioturbation activities were mostly present in the upper sediment layers, but a direct bioturbation influence on the sediment concentration distribution could not be shown. Overall, the contamination load was below baseline toxicity, but considering that several other priority pollutants will also make a contribution to the baseline toxicity, it can be counted as relatively high. Graphical abstract: Image 1 Highlights: Baseline toxicity was below the threshold for lethality at all stations. The stations close to the dumping site were more contaminated. Bioturbation was highest in the upper sediment layers. No direct influence of bioturbation on the sediment concentration could be seen. Higher chemical load might negatively affect the species bioturbation potential.